Isothermal section of the Ni-Mn-Sb ternary system at 773K - Ao W.-Q.; Yu H.-Z.; Liu F.-L.; Liu F.-S.; Li J.-Q.; Du Y.; Liu S.-H.; Shi C.-Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The isothermal section of the Ni-Mn-Sb ternary system at 773 K was measured by means of 117 alloys which were analyzed by using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersion spectroscopy (EDS), and electron probe microanalysis (EPMA) techniques. The existence of 7 binary compounds, namely NiMn, Mn2Sb, MnSb, NiSb2, NiSb, Ni5Sb2, Ni3Sb and 2 ternary compounds, namely Ni2MnSb and NiMnSb were confirmed for this isothermal section. The four binary compounds Ni3Sb (Cu3Ti structure, Pmmn space group), Ni5Sb2 (Ni5Sb2-type structure, C2 space group), NiSb2 (FeS2-type structure, Pnnm space group) and Mn2Sb (Cu2Sb-type structure, P4/nmm space group) in the binary systems Ni-Sb and Mn-Sb were stoichiometric compounds, the homogeneity ranges of which were negligible. However the five single phases in the Ni-Mn system and the two binary compounds MnSb and NiSb showed more or less homogeneity ranges formed by substitution of Mn and Sb for Ni atom. The Heusler compound μ (Ni2MnSb) has L21-type ordered structure with space group Fm-3m, a = 0.6017 nm. And the crystal structure for the Half-Heusler compound κ (NiMnSb) is C1b-type (F-43m) with a = 0.5961 nm. The approximate homogeneity ranges of the two ternary compounds μ and κ at 773 K were investigated.